2011
DOI: 10.1111/j.1470-6431.2011.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of risks of chemical and microbiological contaminants associated with food chains: a cross‐national study

Abstract: The development and implementation of effective systems to identify vulnerabilities in food chains to chemical and microbiological contaminants must take account of consumer priorities and preferences. The present investigation attempted to understand consumer perceptions associated with chemical and microbiological contaminants in four specific food chains (drinking water, farmed salmon, chicken and milk powder). To this end, ten focus group discussions were held in five different countries (Poland, Ireland, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
76
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 41 publications
8
76
0
4
Order By: Relevance
“…Empirical research findings, showing that consumers prefer information attached to products and labels, support this conclusion (Koszewska, 2011). Due to an increasing health consciousness and growing interest in the role of food for maintaining and improving human well-being and consumer health, that is now characterizing the consumer in actual society (Ballestrazzi, Mason, & Nassivera, 2011;Kher et al,2013), vegetables are well recognized for their benefits towards healthy living (Bongoni, Steenbekkers, Verkerk, van Boekel, & Dekker, 2013;Cox et al, 1996;Wootton-Beard & Ryan, 2011), thanks to their protective function against diseases. Numerous studies have shown that consumer's needs for convenience are correlated with food choice (Hjelmar, 2011;Grunert, Brunsø, Bredahl, & Bech, 2001;Verlegh & Candel, 1999).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Empirical research findings, showing that consumers prefer information attached to products and labels, support this conclusion (Koszewska, 2011). Due to an increasing health consciousness and growing interest in the role of food for maintaining and improving human well-being and consumer health, that is now characterizing the consumer in actual society (Ballestrazzi, Mason, & Nassivera, 2011;Kher et al,2013), vegetables are well recognized for their benefits towards healthy living (Bongoni, Steenbekkers, Verkerk, van Boekel, & Dekker, 2013;Cox et al, 1996;Wootton-Beard & Ryan, 2011), thanks to their protective function against diseases. Numerous studies have shown that consumer's needs for convenience are correlated with food choice (Hjelmar, 2011;Grunert, Brunsø, Bredahl, & Bech, 2001;Verlegh & Candel, 1999).…”
Section: Introductionmentioning
confidence: 92%
“…It is evident that consumers are constantly being subjected to a multiplicity of messages, that often seem contradictory, especially when they relate to the quality of food and to issues linked to its safety. Most of the studies, aimed at exploring this topic of the sources of information that affect the purchase choices of consumers, are focused primarily on nutritional and health information (Frewer & Miles, 2003;Kher et al, 2013), the origin of the product, its method of processing and the environmental impact of the production. The demand for eco-sustainable food products and related services is continually growing (Ballestrazzi et al, 2011;Panzone, Wossink, & Southerton, 2013;Vassallo & Saba, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Risiken, die sich beispielsweise nicht durch das eigene Verhalten beeinflussen lassen, werden in der intuitiven Risikoeinschätzung von Laien schwerwiegender bewertet als solche, denen man selbst entgegenwirken kann [7,10,11]. Folglich werden chemische Kontaminationen oftmals als besonders bedrohlich empfunden, da sie aus Sicht der Bevölkerung weniger der eigenen Kontrolle unterliegen und grundsätzlich als ein aufgezwungenes Gesundheitsrisiko angesehen werden [12].…”
unclassified
“…So gibt es derzeit nur eine vergleichsweise geringe Anzahl wissenschaftlicher Studien zur öffentlichen Risikowahrnehmung gegenüber Kontaminanten in Lebensmitteln, die zudem teils geringe Stichprobengrößen aufweisen, aufgrund qualitativer Forschungsansätze [12] oder einer thematischen Zuspitzung auf einzelne Kontaminanten [13][14][15]. Hinzu kommt ein in zweifacher Hinsicht bedeutsames Definitionsproblem: nämlich einerseits die Verwendung unterschiedlicher Definitionen von Kontaminanten im Rahmen wissenschaftlicher Studien (so gelten in einigen Studien z.…”
unclassified
See 1 more Smart Citation